Myelin and Lipid Composition of the Corpus Callosum in Mucopolysaccharidosis Type I Mice. Issue 6 (14th June 2020) - Le, Steven Q.; Nestrasil, Igor; Kan, Shih‐hsin; Egeland, Martin; Cooper, Jonathan D.; Elashoff, David; Guo, Rong; Tolar, Jakub; Yee, Jennifer K.; Dickson, Patricia I.
Abstract: Mucopolysaccharidosis type I (MPS I) is a lysosomal disease with progressive central nervous system involvement. This study examined the lipid, cholesterol, and myelin basic protein composition of white matter in the corpus callosum of MPS I mice. We studied 50 week‐old, male MPS I mice and littermate, heterozygote controls ( n = 12 per group). Male MPS I mice showed lower phosphatidylcholine and ether‐linked phosphatidylcholine quantities than controls ( p < 0.05). Twenty‐two phospholipid or ceramide species showed significant differences in percent of total. Regarding specific lipid species, MPS I mice exhibited lower quantities of sphingomyelin 18:1, phosphatidylserine 38:3, and hexosylceramide d18:1(22:1) mH2 O than controls. Principal components analyses of polar, ceramide, and hexosylceramide lipids, respectively, showed some separation of MPS I and control mice. We found no significant differences in myelin gene expression, myelin basic protein, or total cholesterol in the MPS I mice versus heterozygous controls. There was a trend toward lower proteolipid protein‐1 levels in MPS I mice ( p = 0.06). MPS I mice show subtle changes in white matter composition, with an unknown impact on pathogenesis in this model.